The Movement and Political Controversy of the Islamic Defenders Front In Indonesia - Ifinah Shabirah, Nourah; Binti Samsudin, Farisah Inani; M. Farrel Furqon Amrullah; Aqila Weninggalih; M. Anshori Majid; Bayu Aland Setyo Wibianto (Journal of Political Islam, 2025)
ABSTRACT This study discusses the dynamics of the political movement of the Islamic Defenders Front (FPI) as a religious organization that has had a significant influence on the political landscape of post-reform Indonesia. The FPI was founded with the main objectives of upholding amar ma'ruf nahi munkar (enjoining what is good and forbidding what is evil) and carrying out the role of da'wah (proselytizing) in society. However, over time, the FPI has developed into a socio-political force that is actively involved in various national issues, including large demonstrations such as Aksi 212. This study focuses on three main aspects, namely the ideological goals of the FPI, the forms of political movements carried out, and the controversies and state responses to the existence of this organization. The method used is a qualitative approach with case studies, through primary and secondary data analysis. The results of the study show that the FPI is not only a religious-based moral movement, but also a political actor that influences public policy and the electoral process. Although it was legally disbanded at the end of 2020, the FPI's influence remains present in society through new organizations that carry a similar vision. This study is expected to contribute to understanding the relationship between religion, mass organizations, and the state in Indonesia's democratic system.